Cast a dark shadow - Bogarde, Dirk 1921-1999; Lockwood, Margaret 1916-1990; Walsh, Kay 1911-2005 (Screenbound Pictures, 2021)
"Edward "Teddy" Bare (Dirk Bogarde) is a ruthless schemer who thinks he's hit the big time when he kills his older wife (Mona Washbourne), believing he will inherit a fortune. When things don't go according to plan, Teddy sets his sights on a new victim: wealthy widow Freda Jeffries (Margaret Lockwood). Unfortunately for the unscrupulous criminal, Freda is much more guarded and sassy than his last wife, making separating her from her money considerably more challenging."
Cover: "His sinister plan was murder!"
Original: 1955, Lewis Gilbert Productions
Bildformat 1.66:1 (16:9)
Verlagsnummer SBF669
Keywords: DVD-Video